Spillover Effects From Next Generation EU - Oliver Picek (Intereconomics)
Abstract In July 2020, the European Commission announced its €750 billion package to revive the postpandemic European economy, Next Generation EU. The programme comprises a number of loans and grants that will be funded by taking out European debt. Although the rules on liability sharing for Next Generation EU prevent a significant mutualisation of the debt, European leaders have taken the long-recognised significant first step towards European financial and political unification that stands in stark contrast to the misguided austerity programmes during the European sovereign debt crisis.